More on mobility and sedentism: Changes in adaptation from Upper Paleolithic to Incipient Jomon, Tanegashima Island, southern Japan. - Kazuki Morisaki; Fumie Iizuka; Masami Izuho; Mark Aldenderfer (PLoS ONE)
Sedentism is an adaptive alternative in human societies which is often associated with the emergence of complex societies in the Holocene. To elucidate the factors and processes of the emergence of sedentary societies, continuous accumulation of case studies based on robust evidence from across the world is required. Given abundant archaeological and geological evidence from the late Pleistocene to early Holocene, Tanegashima Island, situated in the southern Japanese Archipelago of the northwestern Pacific Rim, has significant potential to unravel factors and processes of sedentism. Our study evaluates long-term change in hunter-gatherer mobility on Tanegashima Island from the Upper Paleolithic to Incipient Jomon (ca.36,000-12,800 cal BP). Based on Bayesian age modelling, we performed diachronic analyses on lithic toolkit structure, lithic reduction technology, lithic raw material composition, and occupation intensity. The results illustrate that settlement-subsistence strategies on Tanegashima primarily correspond to the change in environmental conditions, mainly food resources, and foragers increased their degrees of sedentism when abundant forest existed. More important is that highly stable sedentism, which is not observed until the Incipient Jomon, depends not only on such a productive environment, but also on the increase in population size. High occupation intensity during the Incipient Jomon on the island is likely attributed to an influx of people from Kyushu proper. Although the relationship between cause and effect of these factors is still to be clarified in future work, our study provides insights on the fundamental causes of sedentism in the temperate forest of the late Pleistocene.